60th ANNIVERSARY OF THE BUDKER INSTITUTE OF NUCLEAR PHYSICS (BINP), SB RAS. 100th ANNIVERSARY OF THE BIRTH OF G I BUDKER : Industrial electron accelerators developed at the Budker Institute of Nuclear Physics, SB RAS. (7th September 2018) - Bryazgin, A A; Kuksanov, N K; Salimov, R A
Abstract: In the early 1960s, work on developing industrial high-power electron accelerators was initiated by Academician G I Budker, the founder and director of the Institute of Nuclear Physics (currently, Budker Institute of Nuclear Physics, BINP). This review describes the arrangements and principles of operation of high-power electron accelerators of the ELV and ILU series designed and constructed at the BINP. Since 1972, 170 ELV and more than 50 ILU machines have been shipped to many countries around the world, most of them still operational. International Atomic Energy Agency surveys rate the BINP as one of the few well-trusted global suppliers of reliable industrial accelerators.